Effects of variations in alloy content and machining parameters on the strength of the intermetallic bonding between a diesel piston and a ring carrier - Acar, Ahu Fahriye (Materiali in tehnologije, 2010)
The intermetallic bonding between an aluminium alloy piston and a cast-iron ring carrier must be able to withstand prolonged exposure to the high-pressure and high-temperature environment of a diesel engine. Weak cohesion may result in the debonding of the ring carrier. Such debonding causes devastating damage to the piston while the engine is in service. Thus, the quality and strength of the intermetallic bonding is very important in piston manufacturing. In the present study, the effects of variations in the alloy content and the machining parameters on the overall strength of the intermetallic bonding are investigated. The defects are determined by ultrasonic inspection. The results indicate that the variation in the alloy content and graphite flakes affects the bond quality adversely. It was determined that the graphite size is a very important parameter. If the graphite size gets smaller, then stronger intermetallic bonding is observed. The graphite accumulation can be resolved by choosing the right amount of alloying elements. The machining process parameters were found to be in effective for the formation of defects on the intermetallic bonding.
Keywords: diezelski motorji; bat; nosilec obročka; intermetalna zveza